To Compare Mean Dash Score at 12 Weeks in Distal Radius Fracture Patients Treated Operatively (ORIF Group) Versus Those Treated Non-Operatively (CAST Group) - Syed Kamran Ahmed, Malik Osama Tanweer, Sadaf Saeed, Aqsa Faiz (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare wrist function by mean of DASH score at 12 weeks in distal radial fracture patients treated operatively (ORIF group) versus those treated non-operatively (CAST group). Methodology: The randomized controlled trial was conducted at The Indus Hospital Karachi, which is a tertiary care hospital from 1st January 2017 to 30th June 2017 and the 12 weeks follow up was taken after the recruitment of the last patient and 96 patients were enrolled. Patients in the operative group were treated with a volar locking plate. Reduction and stabilization of fracture were done with the application of 2.7mm volar locking titanium distal radius anatomically contoured implants. Non-operative Treatment Protocol was that All patients were complete a six weeks immobilization in a splint. One repeated manipulation if needed was accepted in the first 3 weeks. Passive and active finger motion from the starting was encouraged. Formal physiotherapy in this group was started 6 weeks after the removal of the cast. In the twelfth week, the functional assessment was examined by a physiotherapist or orthopaedic resident in both the Cast group and ORIF. Results: Thirty (31.3%) were in operative and 66(68.8%) were in non-operative group. No significant difference were found in age, height, weight, and BMI between both the groups (Mean: 42.7 vs 41.6 years, p=0.644; 156.5 vs 156.4 cm, p=0.962, 61.0 vs 59.5 kg, p=0.557, 24.9 vs 24.5, p=0.395 respectively). Moreover, distribution of gender, dominant hand, and injured hand was also similar in both the groups (p=0.427, p=0.587, and p= 0.673). DASH score were found to be significantly lower in operative group as compared to non-operative cast group (median 17.5 vs 28.8, p<0.0001, mean 16.6 vs 27.9, p<0.0001). Conclusion: At 12 weeks volar locking plates significantly produced better clinical and functional outcomes as compared with the treatment by Cast. The significantly anatomical reduction was more possible to be conserved in the operating group, but in the operative group, early mobilization achieved is the key to better achieving functional outcomes. Keywords: Distal radius extra-articular fractures, DASH score, Wrist function